1990
DOI: 10.1111/j.1464-410x.1990.tb14855.x
|View full text |Cite
|
Sign up to set email alerts
|

Voiding Patterns and Prevalence of Incontinence in Women.: A Questionnaire Survey

Abstract: A detailed questionnaire on the occurrence of irritative and obstructive voiding symptoms, incontinence and the number of childbirths was sent out to 600 women aged between 20 and 79 years, randomly selected from the National Register; 432 (72%) returned the questionnaire and 414 (69%) were evaluable. The frequency of obstructive symptoms such as hesitancy, intermittency and decreased stream was low. Diurnal frequency with voiding intervals less than 3 h were recorded by more than 50% of the women and about 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
3
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(101 citation statements)
references
References 9 publications
7
87
3
4
Order By: Relevance
“…[12][13][14] However, several large studies agree that bothersome, severe incontinence occurs in about 6% of a community population. [15][16][17][18][19] The prevalence increases still further in the physically impaired. Urinary incontinence therefore will commonly occur in stroke survivors as a consequence of their disability even if the stroke is not a cause of the incontinence per se.…”
Section: Prevalence Of Strokementioning
confidence: 99%
“…[12][13][14] However, several large studies agree that bothersome, severe incontinence occurs in about 6% of a community population. [15][16][17][18][19] The prevalence increases still further in the physically impaired. Urinary incontinence therefore will commonly occur in stroke survivors as a consequence of their disability even if the stroke is not a cause of the incontinence per se.…”
Section: Prevalence Of Strokementioning
confidence: 99%
“…However, in a small portion of women sequelae might remain that progress to prolapse and urinary incontinence (3). Although epidemiological data indicate a higher incidence of SUI among multiparous women (4,5), this disorder is observed in 16 to 31% of nulliparous women (6,7). Hormonal alterations resulting from aging, obesity, smoking, chronic cough, and constipation are associated with SUI (8).…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of pelvic floor muscles is generally associated with dysuria and lumbo-pelvic pain 16) . Vaginal delivery is a major factor in the prediction of urinary incontinence regardless of age, because females who have had at least one vaginal delivery experience 2.5 times higher incidence rates of urinary incontinence than women who have not experienced vaginal delivery 17) . Sapsford et al 9) reported contraction of all abdominal muscles during pelvic floor muscle contraction and the contraction was particularly conspicuous in the transversus abdominis muscle and internal and external oblique muscles.…”
Section: Discussionmentioning
confidence: 99%